Determinants of capital structure: Empirical evidence from Philippine publicly listed firms from 2011-2015 - Dela Cruz, Aeson Luiz C. (Animo Repository, 2017)
ll firms share a common objective: to maximize firm value. This will eventually be translated to shareholder wealth maximization. A part of a firm's value maximization strategy is its capital structure. Capital structure decisions affect the firm's financial risk and hence, the firm's value. Across firms, it is interesting to note how capital structures vary - the composition of debt and equity that finances total assets. Previous researches have provided different evidences with regard to various factors affecting a firm's capital structure decisions. Interestingly, differing views with regard to the determinants of capital structure have been established by prior studies and thus, a need for further substantiation exists. This presentation focuses on financing strategies of publicly listed firms in the Philippines as part of their capital structure. In the Philippines, debt financing through bonds or bank loans is a popular and viable option among firms. Debt financing offers tax benefits due to the tax deductibility of interest. On the other hand, equity financing allows diversity of ownership open to potential and current investors. Given such, this presentation aims to examine firm-specific determinants such as age, size, profitability, asset structure and risk and how these factors influence a firm's decision towards the use of financing. The results of this study revealed that asset structure, firm size, profitability and risk are all significant predictors of a firm's level of long- term debt. Our findings are mostly consistent with the results of prior studies. Asset structure, firm size and risk all reported a positive impact on a firm's level of long-term debt while profitability displayed a negative impact on a firm's level of long-term debt. On the contrary, firm age is not a significant predictor of a firm's long-term debt.